2002
DOI: 10.1038/417063a
|View full text |Cite
|
Sign up to set email alerts
|

A new phylum of Archaea represented by a nanosized hyperthermophilic symbiont

Abstract: According to small subunit ribosomal RNA (ss rRNA) sequence comparisons all known Archaea belong to the phyla Crenarchaeota, Euryarchaeota, and--indicated only by environmental DNA sequences--to the 'Korarchaeota'. Here we report the cultivation of a new nanosized hyperthermophilic archaeon from a submarine hot vent. This archaeon cannot be attached to one of these groups and therefore must represent an unknown phylum which we name 'Nanoarchaeota' and species, which we name 'Nanoarchaeum equitans'. Cells of 'N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
555
0
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(581 citation statements)
references
References 23 publications
14
555
0
12
Order By: Relevance
“…Only a few archaeal groups are diderm (Klingl 2014). The only diderm archaea that has been studied in detail is Ignicoccus hospitalis (Huber et al 2002;Küper et al 2010). The volume of Ignicoccus inter-membrane space can be large (20-1000 nm) and contains numerous vesicles that bud from the inner membrane and fuse with the OM (Näther & Rachel 2004).…”
Section: Emvs In Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few archaeal groups are diderm (Klingl 2014). The only diderm archaea that has been studied in detail is Ignicoccus hospitalis (Huber et al 2002;Küper et al 2010). The volume of Ignicoccus inter-membrane space can be large (20-1000 nm) and contains numerous vesicles that bud from the inner membrane and fuse with the OM (Näther & Rachel 2004).…”
Section: Emvs In Archaeamentioning
confidence: 99%
“…Ignicoccus hospitalis usually harbours several cells of the tiny archaeon Nanoarchaeum equitans on its surface (Huber et al 2002). N. equitans has the smallest known genome size for an archaeon (0.49 Mb) and cannot synthesize many essential components, including lipids (Waters et al 2003).…”
Section: Emvs In Archaeamentioning
confidence: 99%
“…It was suggested that this organization may correspond to the ancestral form of reverse gyrase, according to the early emergence of N. equitans at the base of the archaeal domain in both SSU rRNA (Huber et al 2002) and concatenated ribosomal protein trees (Waters et al 2003). However, this archaeon emerged as a sister group of Thermococcales in the reverse gyrase tree (BV = 75% and PP = 0.99, Figure 2) in agreement with a revised position of N. equitans based on a recent and more refined phylogenetic analysis of a concatenation of ribosomal proteins (Brochier et al 2005b).…”
Section: Phylogeny Of the Reverse Gyrasementioning
confidence: 99%
“…Carbon-sulfur cycling in a terrestrial mud volcano T-W Cheng et al 16S rRNA gene analysis Genomic DNA for 16S rRNA gene analyses was extracted from 10-g sediments (from 1, 7, 11, 23 and 31 cm of core c3) and the bubbling fluid (ew01), using the UltraClean Mega Soil DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA, USA) according to the manufacturer's instruction, and stored at -20 1C. Nearly complete 16S rRNA gene sequences were amplified on a Robocycler (Stratagene, La Jolla, CA, USA), using a bacterial forward primer B27F and a universal reverse primer U1492R for bacteria (Lane, 1991), and an archaeal forward primer A8F and a universal reverse primer U1513r for archaea (Huber et al, 2002). The PCR protocol and downstream approaches for purification of PCR products, cloning and sequencing were described previously (Lin et al, 2006).…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%